A Comparative Analysis of the Efficiency of Blockchain Consensus Algorithms: Proof of Work, Proof of Stake, Delegated Proof of Stake, and Practical Byzantine Fault Tolerance - Desman Karya Jaya Zega; Laurensius So Putra Jaya Halawa; Siaman Lase; Melissa Putri Hutabarat (Devitara Innovations, 2026)
The rapid development of blockchain technology has accelerated the adoption of distributed systems across various sectors, including financial services, supply chain management, the Internet of Things (IoT), and digital government. Consensus algorithms play a fundamental role in blockchain by ensuring transaction validity and data consistency without relying on a centralized authority. Since each consensus mechanism exhibits different characteristics, a comparative analysis is required to identify its strengths and limitations. This study aims to analyze and compare the efficiency of four major blockchain consensus algorithms, namely Proof of Work (PoW), Proof of Stake (PoS), Delegated Proof of Stake (DPoS), and Practical Byzantine Fault Tolerance (PBFT). The research employed a comparative literature study by collecting, selecting, and analyzing relevant scientific publications. The comparison was conducted based on transaction throughput, energy efficiency, communication complexity, transaction finality, network characteristics, and fault tolerance. The results indicate that no single consensus algorithm provides optimal performance across all evaluation parameters. PoW offers high security and decentralization but suffers from high energy consumption and low throughput. PoS provides a balanced trade-off among energy efficiency, security, and scalability, while DPoS improves transaction capacity through a delegated validator mechanism. PBFT achieves high throughput and instant transaction finality but is more suitable for permissioned blockchain environments with a limited number of participating nodes. This study proposes a comparative analysis framework that can serve as a reference for selecting an appropriate consensus algorithm based on blockchain implementation requirements.